PEMBENTUKAN MORAL MAHASISWA DALAM MEWUJUDKAN BUDAYA AKADEMIK BERBASIS NILAI ISLAMI (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2019)
Ibnu Khaldun defined education as a transformation of values obtained from experiences as an effort to defence human existance in various forms of culture and continuously developing civilization. Education is urgently needed by all human to keep developing along with the rapid changes in community life. Changes surely drive toward advancement, yet undeniably, it also affects one’s moral. Moral is the quality in human actions that shows which is right or wrong and which is bad or good. Numerous definition explained that moral is significantly important not only for an individual but also for every nation. Todays’ rapid changes has raised various questions related to moral. Many people feel to lose their hold about good norms. Islamic higher education plays important role in determining the good or bad moral of the young generation of the nation. Islamic higher education as an educational institution aiming to produce virtuous, pious, strong faith as well as technologically literate individuals is responsible to nurture students’ moral since they start studying to the day of their graduation and are returned back to the community. This nurturing process can be performed through various approaches and internalization of Islamic values.